Estudo comparativo da pirólise convencional e catalítica de óleo de soja refinado com catalisadores tipo HAlMCM-41 - Rodrigues, Gicélia (2010)
Nowadays, one of the major challenges worldwide is the reduction of greenhouse gas emissions, whose contribution to climatic changes was comproved. The emissions of carbon dioxide from the burning of fossile fuels are the main factor that increases the global warming. Biodiesel is a biodegradable fuel derived from renewable sources that can be obtained by different processes such as pyrolysis, esterification or even transesterification. The pyrolysis reactions refer to the rupture of carbon-carbon binding in hydrocarbons molecules. This reaction is an endothermic process and, therefore, thermodynamically favored by high temperatures and low pressures. The present work has as objective to studiy the thermal and catalytic pyrolysis of soy oil, using acid mesoporosous heterogeneous catalysts (HAlMCM-41). The synthesis and characterization of AlMCM-41 and HAlMCM-41 was performed with different Si/Al ratios. The sample of AlMCM-41 was synthesized by hydrothermal method after that it was submitted to a process of ion exchange to generate the acidic form HAlMCM-41. The catalysts were characterized by X-ray diffraction (XRD) and infrared spectroscopy (IR). Based on the results obtained by infrared spectroscopy analysis, it was possible to indentify the main bands on the structure of AlMCM-41, demonstrating that the calcination method was promising in the elimination of the organic activating substituent. The results of X-ray diffraction showed that the AlMCM-41 was synthesized successfully and with high degree of hexagonal ordination to different Si/Al ratios. A comparative study between thermal pyrolysis and catalytic pyrolysis of refined soybean oil, over catalyst HAlMCM-41 synthesized with different Si/Al ratios, was carried out aiming to study the influence of this catalyst on the conversion rates and in the pyrolysis reaction s activation energy. The results show that mesoporosos catalysts were obtained and that the Si/Al rate of best catalytic activity was equal to 60.